2006
DOI: 10.1177/154431670603000105
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Resource Utilization in Portable Noninvasive Vascular Studies: The Role of Disruptive Technology

Abstract: Purpose Common reasons for avoiding portable noninvasive vascular laboratory (VL) studies include degraded study quality, repetitive stress injuries, the wear and tear of equipment, and inefficiency. We examined the efficiency of portable VL studies in the context of productivity and potential loss of revenue. Methods From January 2005 to March 2005, sonographers in the VL recorded the time required to conduct “in-lab” and portable studies with conventional full-size scanners. A blended average based on freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 3 publications
0
19
0
Order By: Relevance
“…Actual scan time occupied less than 40% of the SG's day across the study sites with the rest spent on patient‐ and non‐patient‐related activities. In our previous report, bedside tests took an average of 17.7 minutes more total test time than examinations done in the VL . As mentioned, we instituted a policy of SG performing several tests before returning to the VL to improve productivity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Actual scan time occupied less than 40% of the SG's day across the study sites with the rest spent on patient‐ and non‐patient‐related activities. In our previous report, bedside tests took an average of 17.7 minutes more total test time than examinations done in the VL . As mentioned, we instituted a policy of SG performing several tests before returning to the VL to improve productivity.…”
Section: Discussionmentioning
confidence: 99%
“…SG at two hospitals at our academic medical center and our OPVL located off‐campus were asked to track and log their daily activities over five consecutive weekdays, including time spent scanning, type of test, delays in patient arrival, preparation for the test, computer entry, lunch breaks, and administrative time (patient‐ and non‐patient‐related). Because our previous study showed that a bedside examination added an average of 17.7 minutes per test compared with one done in the VL, we instructed SG to try and perform several bedside tests per trip to maximize productivity …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Portable examinations, i.e., taking the sonography equipment to the patient, have been linked with increased incidence of musculoskeletal disorders [14]. However, no significant differences were noted in exam efficiency when portable sonographic examinations were completed with laptop-style ultrasound scanners (compact, lightweight) versus conventional mobile ultrasound scanners (full-size ultrasound machine on wheels) [15].…”
Section: Discussionmentioning
confidence: 99%
“…An actual cost study with calculations for supplies, salaries, benefits, equipment, and maintenance costs may be required to arrive at a cost for the procedure. 3 This becomes important in several situations:…”
mentioning
confidence: 99%